Manjšinski status in obmejnost kot platforma odnosa do multikulturnosti - Sedmak, Mateja (Družboslovne razprave, 2018)
The article analyses how members of the Italian and Hungarian minorities in Slovenia view multiculturalism and its manifestations such as ethnic heterogamy transcultural identities, ethnic in/tolerance and ethnic prejudices. The minority status (and bordering position) are in this regard perceived as a platform for attitudes to multiculturalism and a key explanatory factor. The article highlights the presence of the transcultural nature of the minorities and their positive attitudes to multiculturalism, yet also emphasises that the related ethnic sentiment is highly variable, relational and situational. Although one would expect the minorities to more strongly defend the positive effects of multiculturalism, this is not the case. The reason is the confrontation of two ideologies, nationalism and transculturalism, the former interfering in the otherwise transculturally oriented minorities.
Keywords: borderland; Hungarian minority; Italian minority; italijanska narodna manjšina; madžarska narodna manjšina; minorities; multiculturality; multikulturnost; narodne manjšine; obmejnost; Slovenia; Slovenija; transculturality; transkulturnost